Is the damage worth it? Testing handheld XRF as a non-destructive analytical tool for determining biogenic bone and tooth chemistry prior to destructive analyses - Simpson, Emily M. B.; Crowley, Brooke E.; Sturmer, Daniel M. (Frontiers in Environmental Archaeology, 2023)
Isotopic analysis is destructive and requires that a specimen retains its original (biogenic) chemical composition. The relative abundance of calcium and phosphorous (Ca/P) or carbonate and phosphate (CO3/PO4) in a specimen is often used to assess preservation. However, most methods for measuring these proxies are destructive. Moreover, the relationships between Ca/P, CO3/PO4 and isotopic preservation are poorly established. In this study, we assessed the ability of handheld X-ray fluorescence (hXRF) to non-destructively evaluate Ca/P of a specimen’s surface (Ca/Psurface). We first established that Ca/Psurface for a variety of modern bones and teeth from humans and other vertebrates is consistent with values previously obtained using other methods (1.3-2.3). Overall, results were within the expected range, although several human elements yielded slightly larger ratios (between 2.3 and 2.8), suggesting the currently accepted range may need to be expanded. Second, we tested the ability of Ca/Psurface to detect alteration of fossils using twenty Quaternary herbivore teeth from Big Bone Lick, Kentucky. Ten specimens had Ca/Psurface between 1.3 and 2.3 and ten had larger ratios, suggesting alteration. Because most methods measure Ca/P in powder (Ca/Ppowder), we compared Ca/Psurface, Ca/Ppowder, and the enamel subsurface (Ca/Psubsurface). With two exceptions, Ca/Psubsurface and Ca/Ppowder were below 2.3, regardless of Ca/Psurface, suggesting that Ca/Ppowder and Ca/Psubsurface may be unreliable at detecting alteration. We next compared Ca/Psurface, CO3/PO4, and carbon (δ13C) and oxygen (δ18O) isotope values for the fossil teeth. Fourteen specimens were identified as altered or unaltered by both proxies, while six were identified as altered by only one proxy. Specimens with both altered Ca/Psurface and CO3/PO4 had lower, less variable δ13C values than specimens with unaltered Ca/Psurface and CO3/PO4. Median δ18O values were similar between these groups. Specimens with altered Ca/Psurface but unaltered CO3/PO4 isotopically resembled specimens identified as altered by both proxies, while those with unaltered Ca/Psurface and altered CO3/PO4 were more isotopically similar to specimens identified as unaltered by both proxies. Overall, these results suggest that Ca/Psurface is effective at detecting alteration non-destructively, quickly, and affordably, making it an attractive approach for analyzing in situ or museum specimens that are unique or difficult to move.